Acuerdos innovadores de financiación de medicamentos basados en el pago por resultado: análisis descriptivo y buenas prácticas para su implementación en Ecuador - Espín, Jaime (2018)
Context: there are other forms of payment of medicines different from the classic ones that can be an alternative in developing countries.Objective: to carry out a descriptive analysis and good practices for the implementation in Ecuador, of innovative agreements in the payment for results Discussion: this review details the different instruments of the financing of medicines derived from new practices in recent years. This type of agreement implies a change in the paradigm of financing of medicines, mainly in the case of instruments of payment for results, because it pays for the products instead of drugs. The casuistry is extensive and varied, with lights and names in its development and evaluation. The international context has a great diversity of  cases. The existence of a rigorous funding system is based on economic evaluation studies (as in the case of the United Kingdom), or databases that record health outcomes (as in Italy), have given a large number of innovative agreements in these countries.Conclusion: Ecuador is a candidate country to initiate negotiation processes between health companies, the industry and the pharmaceutical industry, to obtain better access, innovative medicines with therapeutic value. Some of the key elements to achieve success in this process is describe in this report